Dynamics of the reaction O(P-3)+H2S -> OH+SH. 2. State-resolved differential cross sections and angular momentum correlations - Costen, M; Hancock, G; Ritchie, G (1999)
Measurements are reported of Doppler resolved polarized laser-induced fluorescence of the OH product of the O(3P) + H2S reaction, leading to estimates of the differential cross sections and angular momentum correlations in the system. O(3P) was produced with translational energy above the barrier to reaction by the polarized 355 nm photolysis of NO2. Three quantum states were studied in detail. For the most populated OH level, v″ = 1, N″ = 6, the scattering for the A″ A doublet was found to be largely sideways/backward, with the remaining energy appearing as product translation, and measurements of average A doublet scattering showed similar behavior for the A′ A doublet. The same scattering dynamics were observed for the v″ = 0, N″ = 13 state. For the rotationless v″ = 1, N″ = 1 state the results were more ambiguous, but if the same distribution of available energy appeared in the SH fragment as deduced for the measurements on rotationally excited OH, then the scattering was seen to be clearly backward. Polarization measurements of the two OH levels with N″ > 1 showed that the angular momentum vector J′ was directed perpendicular to the plane containing the relative velocity vectors of reactants and products. A model of the scattering is proposed through a planar transition state and is able to account qualitatively for these observations of the vector characteristics of the reaction, together with the scalar attributes (quantum state populations) reported in the previous paper. The model predicts that the SH coproduct will be scattered largely forward with respect to the O(3P) atom velocity, with low internal energy, and dominantly in the A″ A doublet.